Exploring the diverse biological significance and roles of fucosylated oligosaccharides - Pekdemir, Burcu; Karav, Sercan (Frontiers in Molecular Biosciences, 2024)
Long since,carbohydrates were thought to be used just as an energy source and structural material.Recent years,with the emergence of the field of glycobiology and advances in glycomics,the biological role of oligosaccharides,a carbohydrate polymer containing a small number of monosaccharides,has been learned as in cell-cell interaction,signal transduction,immune response,pathogen adhesion processes,early embryogenesis and apoptosis.The function of oligosaccharides in these biological roles is diversified by fucosylation,also known as modification of oligosaccharides.Fucosylation process has allowed the identification of more than 100 different oligosaccharide structures which provide functional diversity.ABO blood group and Lewis antigens are among the best known fucosyl-linked oligosaccharides.Also the antigens in the ABO system are composed of various sugar molecules,including fucosylated oligosaccharides and the Lewis antigens are structurally similar to the ABO antigens but differ in the linkage of sugars.Variation in blood group antigen expression affects the host's susceptibility to many infections.However,altered expression of ABO and Lewis antigens is related with prognosis in carcinoma types.In addition,many pathogens recognize and bind to human tissues using a protein receptor with high affinity for the fucose molecule in glycoconjugates,such as lectin.Fucosylated oligosaccharides also play vital roles during fertilization and early embryogenesis.Learning and memory processes such as neurite growth,neurite migration,and synapse formation seen during the development of the brain,which is among the first organs to develop in embryogenesis,are regulated by fucosylated oligosaccharides.In conclusion,this review mentions the vital roles of fucosylated oligosaccharides in biology,drawing attention to their importance in the development of chemical tools to be used in function analysis and the investigation of various therapeutic targets.